DEWAN KOMISARIS INDENPENDEN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jesica dara tista; Elta Try Manda; Bayu Trian Sandi Putra (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
This study aims to determine the effect of independent board of commissioners and profitability on the value of companies in the food and beverage manufacturing subsector listed on the Indonesia Stock Exchange. (BEI). The research population consists of all consumer product business actors registered between 2020 and 2023 on the Indonesia Stock Exchange (BEI). Purposive sampling is the method used for sampling. A total of sixteen businesses were selected based on predetermined criteria. The Indonesian Stock Exchange (BEI) website is a source of the type of secondary data used. Panel regression analysis is a quantitative research method used in this research. Information was collected from manufacturing companies listed on the Indonesian Stock Exchange. Conclusions and research results show that company value is significantly influenced by profitability and an independent board of commissioners.